Communicating hydrocephalus in a case of long-term primary hyperparathyroidism - Ooi, Cheow Peng; Mustafa, Norlaila; Thean, Yew Kew (ASEAN Federation of Endocrine Societies (AFES), 2018)
We present the rare case of a 47-year-old woman with protracted primary hyperparathyroidism complicated by communicating hydrocephalus and cerebellar tonsillar herniation secondary to calvarial thickening. The parathyroid glands remained elusive, despite the use of advanced preoperative imaging modalities and three neck explorations. The serum calcium was optimally controlled with cinacalcet and alfacalcidol. Awareness of this rare complication is essential for early diagnosis and prompt intervention to prevent fatal posterior brain herniation.